Method for reducing secondary phase of ITO target material
By regulating the sintering temperature and using composite sintering aids, the problem of secondary phase generation in ITO targets is solved, and the uniformity and quality of the film are significantly improved.
Patent Information
- Application Number
- CN202411591980.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
During the preparation of ITO targets, secondary phases such as In2O3 and SnO2 are often produced, which will affect the uniformity and quality of the film.
By adjusting the sintering temperature and adding a composite sintering aid, the secondary phase precipitation time is shortened, the sintering temperature is reduced, and the uniformity of the microstructure is improved, thereby reducing the generation of the secondary phase.
It effectively reduces the secondary phase content of the ITO target material and improves the uniformity and quality of the sputtering film.
Smart Images

Figure BDA0005125828530000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of target material manufacturing, and in particular to a method for reducing the secondary phase of an ITO target material. Background Art
[0002] ITO film is a practical transparent conductive material with good conductivity (10 -4 Ω·cm) and excellent optical properties such as high visible light transmittance (>85%), high UV absorption and high infrared light reflectivity (>70%), etc. At the same time, due to its excellent thermal stability and processing performance, indium tin oxide targets are widely used in high-tech fields such as flat panel displays, solar cells and touch screens.
[0003] Patent technical document CN201511032741.9 discloses a method for preparing a high relative density and low resistivity indium tin oxide target. The invention has a simple process, easy to control, reduces the sintering temperature and improves the electrical properties. The equipment is simple and the required production cost is low. The sintered indium tin oxide target has uniform composition, high relative density and low resistivity. Patent technical document CN201810753013.4 discloses a method for preparing a low resistivity ITO target. The method is easy to control, reduces the sintering temperature and promotes densification while improving the electrical properties. The sintered target has a more uniform composition, low resistivity and high relative density. The targets obtained by the above patents all have low resistivity, but in the preparation process of ITO targets, secondary phases such as In2O3 and SnO2 are often produced, which will seriously affect the uniformity and quality of the thin film obtained by sputtering the target. Summary of the invention
[0004] In view of this, the purpose of the present invention is to propose a method for reducing the secondary phase of an ITO target material, so as to solve the problem that the secondary phase content of a conventional target material is high, thereby resulting in poor uniformity of a sputtered film.
[0005] Based on the above purpose, the present invention provides a method for reducing the secondary phase of an ITO target, comprising the following steps:
[0006] S1: mixing indium oxide, tin oxide, a composite sintering aid, a dispersant and deionized water, and ball milling to obtain a ball milling slurry;
[0007] S2: spray granulating the ball mill slurry to obtain composite powder;
[0008] S3: performing cold isostatic pressing on the composite powder to obtain a green embryo;
[0009] S4: firstly put the green blank into a sintering furnace at 400°C, preheat for 5-6h, then heat it to 900°C at 75-80°C / h, keep it at that temperature for 2h, then heat it to 1200°C at 25-30°C / h, keep it at that temperature for 6h, then reduce the temperature to 600°C at 8-10°C / min, cool it to room temperature, and finally anneal it at 600°C for 2h to obtain an ITO target;
[0010] Furthermore, the preparation steps of the composite sintering aid are as follows:
[0011] Magnesium nitrate and aluminum nitrate are dissolved in deionized water and stirred evenly to obtain a mixed solution. Subsequently, H3BO3 and polyethylene glycol are added to the reaction system, reacted at 60-90°C for 10-15h, then dried at 100°C, calcined at 1500°C for 2h, cooled, crushed and ground to obtain a composite sintering aid.
[0012] Furthermore, in step S1, the molar ratio of indium oxide to tin oxide is 0.9-0.92:0.08-0.1.
[0013] Furthermore, the amount of the composite sintering aid added in step S1 is 0.6%-1% of the total weight of indium oxide and tin oxide.
[0014] Furthermore, the amount of the dispersant added in step S1 is 3%-5% of the total weight of indium oxide and tin oxide.
[0015] Furthermore, the amount of deionized water added in step S1 is the same as the total weight of indium oxide and tin oxide.
[0016] Furthermore, the dispersant in step S1 is one of ammonium poly(ethylene glycol) and polyethylene glycol.
[0017] Furthermore, in step S1, the ball milling speed is 400-500 rpm, and the time is 8-10 h.
[0018] Furthermore, the spray granulation in step S2 is carried out in a centrifugal spray dryer, and the operating parameters are an inlet temperature of 65-80°C, an outlet temperature of 50-65°C, and a centrifugal atomizer speed of 6000-14000 r / min.
[0019] Furthermore, in step S3, the cold isostatic pressing pressure is 200-400 MPa, and the holding time is 5-10 min.
[0020] Furthermore, the weight ratio of magnesium nitrate, aluminum nitrate, H3BO3, polyethylene glycol and deionized water is 2-2.1:2-2.2:0.3-0.5:15-20:500-800
[0021] The present invention shortens the secondary phase precipitation time by regulating the sintering temperature, so that the secondary phase content of the target material finally obtained is lower, thereby improving the uniformity of the film after sputtering.
[0022] The present invention reduces the temperature required for sintering by adding a composite sintering aid, on the one hand; and improves the uniformity of the microstructure, which helps to reduce stress concentration at the grain boundaries, thereby reducing the generation of secondary phases, and further improving the uniformity of the film after sputtering.
[0023] The present invention reduces the secondary phase content of the target material and improves the uniformity of the sputtered film by adding a composite sintering aid and improving the sintering temperature. DETAILED DESCRIPTION
[0024] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0025] Embodiment 1: A method for reducing the secondary phase of an ITO target, the specific steps are as follows:
[0026] (1) 2 g of magnesium nitrate and 2 g of aluminum nitrate were dissolved in 500 g of deionized water and stirred to obtain a mixed solution, and then 0.3 g of H3BO3 and 15 g of polyethylene glycol were added to the reaction system, reacted at 60° C. for 10 h, and then dried at 100° C. and calcined at 1500° C. for 2 h, cooled, crushed, and ground to obtain a composite sintering aid;
[0027] (2) 24.9 g of indium oxide, 1.3 g of tin oxide, 0.15 g of a composite sintering aid, 0.78 g of a dispersant, and 26.2 g of deionized water were mixed and ball-milled at 400 rpm for 8 h to obtain a ball-milled slurry;
[0028] (3) spraying and granulating the ball mill slurry in a centrifugal spray dryer to obtain a composite powder, wherein the inlet temperature is 65° C., the outlet temperature is 50° C., and the speed of the centrifugal atomizer is 6000 r / min;
[0029] (4) pressing the composite powder at 200 MPa for 5 min to obtain a green embryo;
[0030] (5) First, place the green blank in a sintering furnace at 400°C and preheat for 5 hours. Then, heat it to 900°C at 75°C / h and keep it at that temperature for 2 hours. Then, heat it to 1200°C at 25°C / h and keep it at that temperature for 6 hours. Then, heat it down to 600°C at 8°C / min and cool it to room temperature. Finally, anneal it at 600°C for 2 hours to obtain an ITO target.
[0031] Embodiment 2: A method for reducing the secondary phase of an ITO target, the specific steps are as follows:
[0032] (1) 2.05 g of magnesium nitrate and 2.1 g of aluminum nitrate were dissolved in 700 g of deionized water and stirred to obtain a mixed solution, and then 0.4 g of H3BO3 and 18 g of polyethylene glycol were added to the reaction system, reacted at 75° C. for 13 h, and then dried at 100° C. and calcined at 1500° C. for 2 h, cooled, crushed, and ground to obtain a composite sintering aid;
[0033] (2) 25.2 g of indium oxide, 1.2 g of tin oxide, 0.11 g of a composite sintering aid, 1.1 g of a dispersant, and 26.4 g of deionized water were mixed and ball-milled at 400 rpm for 8 h to obtain a ball-milled slurry;
[0034] (3) spraying and granulating the ball mill slurry in a centrifugal spray dryer to obtain a composite powder, wherein the inlet temperature is 70° C., the outlet temperature is 60° C., and the speed of the centrifugal atomizer is 10000 r / min;
[0035] (4) pressing the composite powder at 300 MPa for 8 min to obtain a green embryo;
[0036] (5) First, place the green blank in a sintering furnace at 400°C and preheat for 5 hours. Then, heat it to 900°C at 78°C / h and keep it at that temperature for 2 hours. Then, heat it to 1200°C at 28°C / h and keep it at that temperature for 6 hours. Then, heat it down to 600°C at 9°C / min and cool it to room temperature. Finally, anneal it at 600°C for 2 hours to obtain an ITO target.
[0037] Embodiment 3: A method for reducing the secondary phase of an ITO target, the specific steps are as follows:
[0038] (1) 2 g of magnesium nitrate and 2.2 g of aluminum nitrate were dissolved in 700 g of deionized water and stirred to obtain a mixed solution, and then 0.5 g of H3BO3 and 18 g of polyethylene glycol were added to the reaction system, reacted at 80° C. for 14 h, and then dried at 100° C. and calcined at 1500° C. for 2 h, cooled, crushed, and ground to obtain a composite sintering aid;
[0039] (2) 24.9 g of indium oxide, 1.3 g of tin oxide, 0.23 g of a composite sintering aid, 0.78 g of a dispersant, and 26.2 g of deionized water were mixed and ball-milled at 400 rpm for 8 h to obtain a ball-milled slurry;
[0040] (3) spraying and granulating the ball mill slurry in a centrifugal spray dryer to obtain a composite powder, wherein the inlet temperature is 80° C., the outlet temperature is 50° C., and the speed of the centrifugal atomizer is 14000 r / min;
[0041] (4) pressing the composite powder at 400 MPa for 10 min to obtain a green embryo;
[0042] (5) First, place the green blank in a sintering furnace at 400°C and preheat for 6 hours. Then, heat it to 900°C at 75°C / h and keep it at that temperature for 2 hours. Then, heat it to 1200°C at 30°C / h and keep it at that temperature for 6 hours. Then, reduce the temperature to 600°C at 10°C / min, cool it to room temperature, and finally anneal it at 600°C for 2 hours to obtain an ITO target.
[0043] Embodiment 4: A method for reducing the secondary phase of an ITO target, the specific steps are as follows:
[0044] (1) 2.1 g of magnesium nitrate and 2.2 g of aluminum nitrate were dissolved in 800 g of deionized water and stirred to obtain a mixed solution. Subsequently, 0.5 g of H3BO3 and 20 g of polyethylene glycol were added to the reaction system, reacted at 90° C. for 15 h, then dried at 100° C., and calcined at 1500° C. for 2 h, cooled, crushed, and ground to obtain a composite sintering aid.
[0045] (2) 25.4 g of indium oxide, 1.1 g of tin oxide, 0.26 g of a composite sintering aid, 1.3 g of a dispersant, and 26.5 g of deionized water were mixed and ball-milled at 400 rpm for 8 h to obtain a ball-milled slurry;
[0046] (3) spraying and granulating the ball mill slurry in a centrifugal spray dryer to obtain a composite powder, wherein the inlet temperature is 80° C., the outlet temperature is 65° C., and the speed of the centrifugal atomizer is 14000 r / min;
[0047] (4) pressing the composite powder at 400 MPa for 10 min to obtain a green embryo;
[0048] (5) First, place the green blank in a sintering furnace at 400°C and preheat for 6 hours. Then, heat it to 900°C at 80°C / h and keep it at that temperature for 2 hours. Then, heat it to 1200°C at 30°C / h and keep it at that temperature for 6 hours. Then, heat it to 600°C at 10°C / min and cool it to room temperature. Finally, anneal it at 600°C for 2 hours to obtain an ITO target.
[0049] Comparative Example 1: A method for preparing an ITO target material, the specific steps are as follows:
[0050] (1) 2.05 g of magnesium nitrate and 2.1 g of aluminum nitrate were dissolved in 700 g of deionized water and stirred to obtain a mixed solution, and then 0.4 g of H3BO3 and 18 g of polyethylene glycol were added to the reaction system, reacted at 75° C. for 13 h, and then dried at 100° C. and calcined at 1500° C. for 2 h, cooled, crushed, and ground to obtain a composite sintering aid;
[0051] (2) 25.2 g of indium oxide, 1.2 g of tin oxide, 0.11 g of a composite sintering aid, 1.1 g of a dispersant, and 26.4 g of deionized water were mixed and ball-milled at 400 rpm for 8 h to obtain a ball-milled slurry;
[0052] (3) spraying and granulating the ball mill slurry in a centrifugal spray dryer to obtain a composite powder, wherein the inlet temperature is 70° C., the outlet temperature is 60° C., and the speed of the centrifugal atomizer is 10000 r / min;
[0053] (4) pressing the composite powder at 300 MPa for 8 min to obtain a green embryo;
[0054] (5) First, place the green blank into a sintering furnace at 400°C and preheat for 5 hours. Then, heat it to 900°C at 78°C / h and keep it at that temperature for 2 hours. Then, heat it to 1200°C at 28°C / h and keep it at that temperature for 6 hours. Then, heat it down to 600°C at 9°C / min and anneal it at 600°C for 2 hours to obtain an ITO target.
[0055] Comparative Example 2: A method for preparing an ITO target material, which differs from Example 2 in that H3BO3 is not added, and the remaining steps are the same as Example 2. The specific steps are as follows:
[0056] (1) 2.05 g of magnesium nitrate and 2.1 g of aluminum nitrate were dissolved in 700 g of deionized water and stirred to obtain a mixed solution, and then 18 g of polyethylene glycol was added to the reaction system, reacted at 75° C. for 13 h, and then dried at 100° C. and calcined at 1500° C. for 2 h, cooled, crushed, and ground to obtain a composite sintering aid;
[0057] (2) 25.2 g of indium oxide, 1.2 g of tin oxide, 0.11 g of a composite sintering aid, 1.1 g of a dispersant, and 26.4 g of deionized water were mixed and ball-milled at 400 rpm for 8 h to obtain a ball-milled slurry;
[0058] (3) spraying and granulating the ball mill slurry in a centrifugal spray dryer to obtain a composite powder, wherein the inlet temperature is 70° C., the outlet temperature is 60° C., and the speed of the centrifugal atomizer is 10000 r / min;
[0059] (4) pressing the composite powder at 300 MPa for 8 min to obtain a green embryo;
[0060] (5) First, place the green blank in a sintering furnace at 400°C and preheat for 5 hours. Then, heat it to 900°C at 78°C / h and keep it at that temperature for 2 hours. Then, heat it to 1200°C at 28°C / h and keep it at that temperature for 6 hours. Then, heat it down to 600°C at 9°C / min and cool it to room temperature. Finally, anneal it at 600°C for 2 hours to obtain an ITO target.
[0061] Comparative Example 3: A method for preparing an ITO target material, which differs from Example 2 in that polyethylene glycol is not added, and the remaining steps are the same as Example 2. The specific steps are as follows:
[0062] (1) 2.05 g of magnesium nitrate and 2.1 g of aluminum nitrate were dissolved in 700 g of deionized water and stirred to obtain a mixed solution, and then 0.4 g of H3BO3 was added to the reaction system, reacted at 75° C. for 13 h, and then dried at 100° C. and calcined at 1500° C. for 2 h, cooled, crushed, and ground to obtain a composite sintering aid;
[0063] (2) 25.2 g of indium oxide, 1.2 g of tin oxide, 0.11 g of a composite sintering aid, 1.1 g of a dispersant, and 26.4 g of deionized water were mixed and ball-milled at 400 rpm for 8 h to obtain a ball-milled slurry;
[0064] (3) spraying and granulating the ball mill slurry in a centrifugal spray dryer to obtain a composite powder, wherein the inlet temperature is 70° C., the outlet temperature is 60° C., and the speed of the centrifugal atomizer is 10000 r / min;
[0065] (4) pressing the composite powder at 300 MPa for 8 min to obtain a green embryo;
[0066] (5) First, place the green blank in a sintering furnace at 400°C and preheat for 5 hours. Then, heat it to 900°C at 78°C / h and keep it at that temperature for 2 hours. Then, heat it to 1200°C at 28°C / h and keep it at that temperature for 6 hours. Then, heat it down to 600°C at 9°C / min and cool it to room temperature. Finally, anneal it at 600°C for 2 hours to obtain an ITO target.
[0067] Comparative Example 4: A method for preparing an ITO target material, which differs from Example 2 in that H3BO3 and polyethylene glycol are not added, and the remaining steps are the same as Example 2. The specific steps are as follows:
[0068] (1) 2.05 g of magnesium nitrate and 2.1 g of aluminum nitrate were dissolved in 700 g of deionized water, stirred evenly to obtain a mixed solution, then reacted at 75° C. for 13 h, then dried at 100° C., and calcined at 1500° C. for 2 h, cooled, crushed, and ground to obtain a composite sintering aid;
[0069] (2) 25.2 g of indium oxide, 1.2 g of tin oxide, 0.11 g of a composite sintering aid, 1.1 g of a dispersant, and 26.4 g of deionized water were mixed and ball-milled at 400 rpm for 8 h to obtain a ball-milled slurry;
[0070] (3) spraying and granulating the ball mill slurry in a centrifugal spray dryer to obtain a composite powder, wherein the inlet temperature is 70° C., the outlet temperature is 60° C., and the speed of the centrifugal atomizer is 10000 r / min;
[0071] (4) pressing the composite powder at 300 MPa for 8 min to obtain a green embryo;
[0072] (5) First, place the green blank in a sintering furnace at 400°C and preheat for 5 hours. Then, heat it to 900°C at 78°C / h and keep it at that temperature for 2 hours. Then, heat it to 1200°C at 28°C / h and keep it at that temperature for 6 hours. Then, heat it down to 600°C at 9°C / min and cool it to room temperature. Finally, anneal it at 600°C for 2 hours to obtain an ITO target.
[0073] Performance Testing
[0074] Density: The target materials obtained in the embodiment and the comparative example were tested according to the water displacement method. The test results are shown in Table 1.
[0075] Secondary phase content: The target materials obtained in the embodiment and the comparative example were subjected to microstructural testing, and the test results are shown in Table 1;
[0076] Thickness uniformity: The target materials obtained in the embodiment and the comparative example were subjected to magnetron sputtering. The substrate was a glass substrate. The thickness uniformity was calculated according to the following formula:
[0077]
[0078] Table 1 Performance test results
[0079] Density(%) Secondary phase content (%) Thickness uniformity (%) Example 1 98.4 0.3 7.63 Example 2 99.1 0.2 7.47 Example 3 98.8 0.3 7.81 Example 4 98.1 0.4 7.52 Comparative Example 1 97.3 2.3 12.45 Comparative Example 2 98.5 2.7 17.53 Comparative Example 3 98.7 3.3 20.71 Comparative Example 4 98.5 5.3 37.57
[0080] Data analysis: It can be seen from Examples 1-3 that the target material obtained by the method of reducing the secondary phase of the ITO target material of the present invention has a relatively excellent density, not less than 98%, and a low secondary phase content, not exceeding 0.5%; and the film obtained after sputtering has relatively excellent thickness uniformity.
[0081] It can be seen from Example 2 and Comparative Example 1 in Table 1 that the present invention shortens the secondary phase precipitation time by adjusting the specific parameters of the sintering process, so that the secondary phase content of the final target material is lower, thereby improving the uniformity of the film after sputtering.
[0082] It can be seen from Example 2 and Comparative Examples 2, 3, and 4 that the present invention reduces the temperature required for sintering by adding a composite sintering aid, and adds H3BO3 and polyethylene glycol in the process of preparing the composite sintering aid, so that the effect of the composite sintering aid is better. On the one hand, doping elements are introduced into the composite sintering aid to improve its sintering performance. On the other hand, H3BO3 and polyethylene glycol play a complexing and dispersing role therein, which ultimately reduces the secondary phase content of the target material and improves the uniformity of the sputtered film.
[0083] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A method for reducing the secondary phase of an ITO target, characterized in that: The following steps are involved: S1: mixing indium oxide, tin oxide, a composite sintering aid, a dispersant and deionized water, and ball milling to obtain a ball milling slurry; S2: spray granulating the ball mill slurry to obtain composite powder; S3: performing cold isostatic pressing on the composite powder to obtain a green embryo; S4: firstly put the green blank into a sintering furnace at 400°C, preheat for 5-6h, then heat it to 900°C at 75-80°C / h, keep it at that temperature for 2h, then heat it to 1200°C at 25-30°C / h, keep it at that temperature for 6h, then reduce the temperature to 600°C at 8-10°C / min, cool it to room temperature, and finally anneal it at 600°C for 2h to obtain an ITO target; The preparation steps of the composite sintering aid are as follows: Magnesium nitrate and aluminum nitrate are dissolved in deionized water and stirred evenly to obtain a mixed solution. Subsequently, H3BO3 and polyethylene glycol are added to the reaction system, reacted at 60-90°C for 10-15h, then dried at 100°C, calcined at 1500°C for 2h, cooled, crushed and ground to obtain a composite sintering aid.
2. The method for reducing the secondary phase of an ITO target according to claim 1, characterized in that: The molar ratio of indium oxide to tin oxide in step S1 is 0.9-0.92:0.08-0.1; the amount of the composite sintering aid added is 0.6%-1% of the total weight of indium oxide and tin oxide.
3. The method for reducing the secondary phase of an ITO target according to claim 1, characterized in that: In step S1, the amount of the dispersant added is 3%-5% of the total weight of indium oxide and tin oxide; the amount of deionized water added is the same as the total weight of indium oxide and tin oxide.
4. The method for reducing the secondary phase of an ITO target according to claim 1, characterized in that: The ball milling speed in step S1 is 400-500 rpm, and the time is 8-10 hours.
5. The method for reducing the secondary phase of an ITO target according to claim 1, characterized in that: The spray granulation in step S2 is carried out in a centrifugal spray dryer, and the operating parameters are an inlet temperature of 65-80°C, an outlet temperature of 50-65°C, and a centrifugal atomizer speed of 6000-14000 r / min.
6. The method for reducing the secondary phase of an ITO target according to claim 1, characterized in that: The cold isostatic pressing pressure in step S3 is 200-400 MPa, and the holding time is 5-10 min.
7. The method for reducing the secondary phase of an ITO target according to claim 1, characterized in that: The weight ratio of the magnesium nitrate, aluminum nitrate, H3BO3, polyethylene glycol and deionized water is 2-2.1:2-2.2:0.3-0.5:15-20:500-800.
Citation Information
Patent Citations
Preparation method of indium tin oxide target with high relative density and low resistivity
CN105669186B
Preparation method of low-resistivity ITO (indium tin oxide) target
CN108585831A
Ito sputtering target material and method for producing same
CN105308002A
Preparation method of ITO sputtering target material
CN115159975A
Indium tin oxide target material with low tin oxide content and preparation method thereof
CN118495924A